2020
DOI: 10.1101/2020.02.13.938258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term single-cell imaging and simulations of microtubules reveal driving forces for wall pattering during proto-xylem development

Abstract: 42Plants are the tallest organisms on Earth; a feature sustained by solute-transporting 43 xylem vessels in the plant vasculature. The xylem vessels are supported by strong 44 cell walls that are assembled in intricate patterns. Cortical microtubules direct wall 45 deposition and need to rapidly re-organize during xylem cell development. We 46 established long-term live-cell imaging of single Arabidopsis cells undergoing proto-47 xylem trans-differentiation, resulting in spiral wall patterns, to investigate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…Therefore, KTN1 is not required for the cell-autonomous activity of miR165/6. KTN1-regulated microtubule organization was reported to be required for the spiral cell wall thickening in the protoxylem (Schneider et al, 2021). Our results here showed that expression of MIR165A in the stele results in ectopic formation of protoxylem cell wall patterns in the ktn1-20 background, which suggests that KTN1"s role in protoxylem cell wall patterning is likely indirect, properly through its regulation of xylem cell fates via miR165/6.…”
Section: Ktn1 Is Dispensable For the Cell Autonomous Activity Of Mir165/6supporting
confidence: 49%
“…Therefore, KTN1 is not required for the cell-autonomous activity of miR165/6. KTN1-regulated microtubule organization was reported to be required for the spiral cell wall thickening in the protoxylem (Schneider et al, 2021). Our results here showed that expression of MIR165A in the stele results in ectopic formation of protoxylem cell wall patterns in the ktn1-20 background, which suggests that KTN1"s role in protoxylem cell wall patterning is likely indirect, properly through its regulation of xylem cell fates via miR165/6.…”
Section: Ktn1 Is Dispensable For the Cell Autonomous Activity Of Mir165/6supporting
confidence: 49%
“…In addition, Wallin (WAL) is recruited to the PM at pit boundaries by Boundary of ROP domain1 (BRD1) to promote actin assembly, thereby shaping pit borders as well (Sugiyama et al, 2019). Furthermore, using long-term live-cell imaging technology in Arabidopsis cells undergoing protoxylem transdifferentiation, the local recruitment of the microtubulebound nucleation factor KATANIN was observed during the patterning of spiral walls (Schneider et al, 2020). These mechanisms might be applicable to cell wall compartmentalization in other cell types as well, although visualizing this process is still technically challenging.…”
Section: Cell Wall Compartmentalizationmentioning
confidence: 99%
“…The higher density of secondary cell wall coils in the PX of icr5 is in line with a role of ICR5 in destabilization of microtubules. Based on a combination of experimental work and computer simulation, Schneider et al recently proposed that microtubule destabilization takes place during secondary cell wall formation in PX (Schneider et al, 2020). It is possible that ICR5 functions during this microtubule destabilization.…”
Section: Discussionmentioning
confidence: 99%